Level of creative thinking ability of students in solving numeracy problems - Yudi Yunika Putra; Joko Sutrisno AB; Imam Fitri Rahmadi (Journal of Research and Advances in Mathematics Education)
Creative thinking plays an important role in the development of new ideas in mathematical solutions that are positively correlated with crucial 21st century skills. This study aims to determine the level of students' creative thinking skills in solving numeracy problems. The research subjects consisted of 30 fourth grade elementary school students in Central Bangka Regency, Bangka Belitung Islands Province. The research method used descriptive research with a qualitative approach. The data collection technique used a written test of 5 questions. The questions were based on the Minimum Competency Assessment (AKM) numeracy test from the Education Assessment Center (Pusmendik). The data test test were analyzed descriptively on the level of creative thinking ability. The results showed that 7% of students reached level 2 in creative thinking, able to solve with original solutions but did not reach fluency or flexibility. Most students reached level 0 and 1 respectively 53% and 40%, the solution did not meet the originality (novelty), fluency, and or flexibility. The low level of creative thinking of elementary school students illustrates that the learning process tends not to be on a new and flexible problem solving process, it is recommended to implement a learning model based on open problem solving or project-based learning that stimulates creative thinking skills.